PENGGUNAAN LAYANAN KONSELING KELOMPOK UNTUK MENINGKATKAN RASA PERCAYA DIRI DALAM BELAJAR - Yondariwati Yondariwati; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine the increase in self-confidence in learning after attending a group counseling services in the students. The problem in this study was the low of students’ self-confidence. The question in this study was "Is there an increase in self-confidence in students' learning after attending a group counseling services to the students?". The method used in this study was pre-experimental design methods with one-group pretest-posttest design. Subject of this study were eight students of grade XI. Data collection techniques in this study using the scale techniques and supported by unstructured observation.The results obtained in this study indicate that there was an increase in self-confidence in learning after attending a group counseling services, as indicated from the results of the data analysis using the Wilcoxon test, from the pretest and posttest results we obtained p = 0.012: p 0.05. Then, Ho was rejected and Ha was accepted, which mean that there was an increase in self-confidence in learning after attending a counseling group. The conclusion of this study was that there was an increase of self-confidence in learning after attending a group counseling services in the students. The advice given are: (1) The students should be able to take part in group counseling services, thus they can increas their confidence in learning, (2) Counselling teachers should conduct group counseling activities to help students improve their self-confidence in learning.kata kunci: bimbingan konseling, konseling kelompok, percaya diri dalam belajar